Gendered Experiences of Parent–Child Communication on Sexual and Reproductive Health Issues: A Qualitative Study Employing Community-Based Participatory Methods among Primary Caregivers and Community Stakeholders in Rural South-Western Uganda - Achen, Dorcus; Nyakato, Viola N.; Akatukwasa, Cecilia; Kemigisha, Elizabeth; Mlahagwa, Wendo; Kaziga, Ruth; Ruzaaza, Gad Ndaruhutse; Rukundo, Godfrey Zari; Michielsen, Kristien; Neema, Stella; Coene, Gily (International Journal of Environmental Research and Public Health, 2022)
Open and positive parent–child communication about sexual and reproductive health (SRH) is known to reduce negative SRH outcomes for young people. However, socio-cultural influences can inhibit meaningful SRH communication. Restrictive gender norms threaten the SRH of adolescents, as they make adolescent boys more likely to engage in risky sexual behavior and make girls more vulnerable to negative SRH outcomes. This study intended to critically understand the impact of gender norms and expectations on parent–child SRH communication in rural southwestern Uganda. Methods: The study adopted a community-based participatory approach using community stakeholder engagement meetings (n = 2), in-depth interviews (n = 12), and three focus group discussions with parents (n = 18). The study considered biological parents, step-parents, grandparents, uncles and aunties, as long as they were primary caregivers of adolescents aged 10–14. Results: Participants elaborated on the socio-cultural aspects that shaped their experiences of parent–child SRH communication such as cultural gender norms, religion, and media influences. They also referred to socio-economic challenges, lack of knowledge, and the role of peers and schools. Conclusions: There is need for community-based interventions to improve parent–child SRH communication to address the deeply rooted cultural and gender contexts in rural southwestern Uganda.
Keywords: Parent–child communication; Sexual and reproductive health; Culture; Gender